The rise of Central Banks : state power in financial capitalism - Wansleben, Leon, 1982- (Harvard University Press, 2023)
Central banks are supposed to stabilize markets, yet decades of mounting central bank power have seen wave after wave of financial crisis. Leon Wansleben offers novel explanations for the rise of central banks and the problematic implications of their finance-dependent policies.